Seismic behavior and damage evolution of corroded RC columns designed for bending failure in an artificial climate. (April 2022) - Shang, Zhigang; Zheng, Shansuo; Zheng, Hao; Li, YaLin; Dong, Jinqi
Abstract: Several past studies have shown that artificial climate simulation techniques can address obstacles in electrochemical corrosion methods. However, few experimental studies have investigated the seismic behavior of corroded reinforced concrete (RC) columns in an artificial climate. Therefore, in this study, seven corroded RC column specimens that experienced bending failure were subjected to pseudostatic tests after artificial climate accelerated corrosion tests. The variable parameters of the specimens were the corrosion degree of the reinforcement and axial compression ratio. The seismic behavior of the columns corresponding to corrosion-induced cracks, corrosion morphology of the steel bars, failure process, hysteretic behavior, skeleton curve, ductility, stiffness, energy dissipation capacity and flexural performance were investigated. Based on the test results, a two-parameter damage model was established to evaluate the damage evolution of the corroded RC columns. The results of the test and analysis revealed that the surface characteristics of corroded steel bars under the artificial climate were similar to those in the natural environment. The corrosion ratio of the reinforcement at the RC column edge was higher than that at the middle region of the specimen. As the corrosion degree increased, the seismic behavior of the specimen deteriorated continuously. As the axial compression ratio increased, the bearing capacity and bending bearing capacity initially increased and then decreased since the failure pattern of the columns changed from large eccentric compression failure to small eccentric compression failure. The corrosion and axial compression ratio accelerated the damage development of the RC columns. The proposed damage model accorded with the experimental phenomena before yielding and under the ultimate state, but underestimated the damage between the yield state and the peak state.